A reckless love [large type] - White, Beth, 1957- (White, Beth, 1957- Daughtry House, 2021)
"In the fine tradition established by her Southern grandmama, Aurora Daughtry has recently orchestrated the marriage of her eldest sister and facilitated her middle sister's engagement. She also rejoices in her part in transforming the family's dilapidated plantation manor into a luxurious and lucrative resort hotel. Just when it seems there is nothing left to absorb her considerable talent for managing people, in walks federal deputy marshal Zane Sager. But Zane is not at Daughtry House for a vacation. He's tracking a killer and collecting two key witnesses to a federal judge's murder. Aurora takes it upon herself to disabuse the cynical lawman of his conviction that the world--and God in particular--is out to get him. But just as she's on the verge of cracking Zane's defenses, the man he is after reminds him that no one he loves is safe. Ever" --